2014
DOI: 10.1186/1472-6874-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Vocal local versus pharmacological treatments for pain management in tubal ligation procedures in rural Kenya: a non-inferiority trial

Abstract: BackgroundVocal local (VL) is a non-pharmacological pain management technique for gynecological procedures. In Africa, it is usually used in combination with pharmacological analgesics. However, analgesics are associated with side-effects, and can be costly and subject to frequent stock-outs, particularly in remote rural settings. We compared the effectiveness of VL + local anesthesia + analgesics (the standard approach), versus VL + local anesthesia without analgesics, on pain and satisfaction levels for wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The multivariable analysis confirmed that the vocal distraction analgesia was a protective factor for pain (VAS > 4) (OR adj = 0.30; 95%CI: 0.11-0.78) and the other investigated factors resulted not significantly related to pain. This result agrees with the study carried out in Kenya [29], in which the majority of respondents were over 30 (78%), married (96%) with 3 or more children (99%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The multivariable analysis confirmed that the vocal distraction analgesia was a protective factor for pain (VAS > 4) (OR adj = 0.30; 95%CI: 0.11-0.78) and the other investigated factors resulted not significantly related to pain. This result agrees with the study carried out in Kenya [29], in which the majority of respondents were over 30 (78%), married (96%) with 3 or more children (99%).…”
Section: Discussionsupporting
confidence: 92%
“…A study in Kenya of 1000 women has demonstrated the effectiveness of vocal distraction as a method for reducing the perception of pain in the inability to use anaesthetic drugs [29]. In this study, women were divided into two groups: in one they were subjected to local anaesthesia and vocal distraction during the tying of the salpinges with a mini-laparotomy technique without the use of opioid analgesics, while in the control group the latter was administered.…”
Section: Discussionmentioning
confidence: 99%
“…Danis et al [22] compared postpartum salpingectomy to post-partum bilateral tubal ligation in a retrospective consecutive cohort, and found significantly longer operative times for those undergoing post-partum salpingectomy (71.44 min ± 5.81 vs. 59.13 min ± 16 min p = 0.003) similar to our own findings. Wagar et al [21] reported a shorter median operative time for post-partum salpingectomy compared to bilateral tubal ligation immediately following vaginal delivery (30)(31)(32)(33)(34)(35)(36)(37)(38) vs. 34 min [IQR 26-42], p = 032). However, 97% of post-partum salpingectomy cases utilized a bipolar electrocautery device [21].…”
Section: Discussionmentioning
confidence: 99%
“…The use of post-partum-female permanent contraception varies widely by country [27]. Descriptions on the use of post-partum tubal ligations for permanent contraception and complication rates are available for at least two low and middle-income countries [28,29], and descriptions on how to increase accessibility by alternative approaches to analgesia are also available [30]. Our procedure described here would allow access not only to contraception, but also potential ovarian cancer risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Nonpharmacological management, e.g., music, conversation, and support by the medical personnel during the procedure, can also significantly reduce anxiety and pain during hysteroscopy, which has also been demonstrated in other surgical procedures with the patient awake [43]. This reduces the need for pharmacological pain relief and increases patient satisfaction with the care received [44].…”
Section: Pain Complaintsmentioning
confidence: 96%